Effect of prematurity and low birth weight in visual abilities and school performance. (December 2016) - Perez-Roche, T.; Altemir, I.; Giménez, G.; Prieto, E.; González, I.; Peña-Segura, J.L.; Castillo, O.; Pueyo, V.
Abstract: Background: Prematurity and low birth weight are known risk factors for cognitive and developmental impairments, and school failure. Visual perceptual and visual motor skills seem to be among the most affected cognitive domains in these children. Aims: To assess the influence of prematurity and low birth weight in visual cognitive skills and school performance. Methods: We performed a prospective cohort study, which included 80 boys and girls in an age range from 5 to 13. Subjects were grouped by gestational age at birth (preterm, <37 weeks; term, 37–42 weeks) and birth weight (small for gestational age (SGA), <10th centile; appropriate weight for gestational age (AGA), ≥10th centile). Each child underwent full ophthalmologic assessment and standardized testing of visual cognitive abilities (Test of Visual Perceptual Skills and Test of Visual Analysis Skills). Parents completed a questionnaire on school performance in children. Results: Figure-ground skill and visual motor integration were significantly decreased in the preterm birth group, compared with term control subjects (figure-ground: 45.7 vs 66.5, p = 0.012; visual motor integration, TVAS: (9.9 vs 11.8, p = 0.018), while outcomes of visual memory (29.0 vs 47.7, p = 0.012), form constancy (33.3 vs 52.8, p = 0.019), figure-ground (37.4 vs 65.6, p = 0.001), and visual closure (43.7 vs 62.6 p = 0.016) testing were lower in the SGA (vs AGA) group. Visual cognitive difficulties corresponded with worse performance in mathematics (r = 0.414, p = 0.004) and reading (r = 0.343, p = 0.018). Conclusion: Specific patterns of visual perceptual and visual motor deficits are displayed by children born preterm or SGA, which hinder mathematics and reading performance.